2019
DOI: 10.1111/cfs.12684
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the essence of enabling child participation within child protection services

Abstract: The chances that children have to participate in child protection services are largely contingent upon the attitudes and skills of case managers. They have a crucial role in ensuring that a child's voice is being listened to and acknowledged in often sensitive dialogues. Therefore, the aim of this study is to investigate what case managers need to facilitate child participation. By handing case managers a participation toolbox developed by children and through the use of reflexive monitoring in action, we elab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 22 publications
3
45
0
4
Order By: Relevance
“…Child welfare workers in Norway, the United Kingdom, and the United States perceived children’s participation as hearing the child’s opinion combined with informing them (Križ & Skivenes, 2017). Van Bijleveld et al (2020) found that child participation was defined by different concepts such as “involving children,” “being part of the process,” “giving their opinion,” “being taken seriously,” and “being listened to”; nevertheless, when reflecting on actual practices, the conversation mainly focused on “providing to” and “gathering information” from children. Furthermore, Alfandari’s (2017) study showed that interaction with children was a matter of “seeing” them rather than communicating with them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Child welfare workers in Norway, the United Kingdom, and the United States perceived children’s participation as hearing the child’s opinion combined with informing them (Križ & Skivenes, 2017). Van Bijleveld et al (2020) found that child participation was defined by different concepts such as “involving children,” “being part of the process,” “giving their opinion,” “being taken seriously,” and “being listened to”; nevertheless, when reflecting on actual practices, the conversation mainly focused on “providing to” and “gathering information” from children. Furthermore, Alfandari’s (2017) study showed that interaction with children was a matter of “seeing” them rather than communicating with them.…”
Section: Resultsmentioning
confidence: 99%
“…The social position of children has changed considerably in recent decades, recognizing children as social actors (McCafferty, 2017; Röbäck & Höjer, 2009). Nevertheless, despite legislation and policies obligating children’s participation, it remains a complex area of practice (Kosher & Ben-Arieh, 2019; Van Bijleveld et al, 2020).…”
mentioning
confidence: 99%
“…However, this is not going to occur until the ongoing negative perceptions held by practitioners regarding children's capacity are addressed. As Bijleveld et al (2019, p. 8) identify, changing attitudes both conscious and deep‐seated is not easy. In this study, practitioners identified the highest barriers for children voices not being asked or heard was due to the respondent's perception of vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of practitioners believe in the importance of hearing children's voices in family support services and believe their practice to be child‐inclusive, the survey findings point to a gap between respondents' intent and their reported level of children's actual participation. The complex interplay of underlying barriers, even with positive attitudes and appropriate tools, is identified as reducing the potential for behavioural change (Bijleveld et al 2019, p. 6). Identified in the literature is that to authentically and meaningfully empower children's voices, good practice begins first with considering and clarifying the way children and childhood are conceptualized (Christensen & James, 2017, p. 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation